The Interaction Between Concrete-Pictorial-Abstract (CPA) Approach and Elementary Students’ Self-Efficacy In Learning Mathematics - Aan Yuliyanto; Turmudi Turmudi; Mubiar Agustin; Hafiziani Eka Putri; Idat Muqodas (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractDriven by the elementary students’ low self-efficacy (SE) in learning mathematics, this study aims to delve deeper into the interaction between learning based on Mathematical Prior Ability (MPA) and the improvement of students' SE after the implementation of Concrete-Pictorial-Abstract (CPA) approach. In total, 119 elementary school students from Purwakarta, Subang, Karawang dan Bekasi participated. Both tests and non-tests were used as the instruments of this study. Using a quasi-experimental design with a nonequivalent pretest-posttest control group, a two-way ANOVA was used as the technical analysis of the data. The research results revealed that the learning factors are higher than 0.05 i.e. (0.235), the significance of the MPA factor is smaller than 0.05 i.e. (0.030), and the significance of the interaction factor (Learning MPA) is higher than 0.05 i.e. (0.301). It can be concluded that there is an interaction between learning (CPA and conventional) based on MPA and the students’ SE. Thus, the CPA approach can be used to enhance the students’ SE so that they can learn with higher confidence.Keywords: concrete pictorial abstract, self-efficacy, mathematical prior ability. AbstrakDilatarbelakangi oleh rendahnya efikasi diri siswa sekolah dasar dalam pembelajaran matematika, penelitian ini bertujuan untuk menyelidiki lebih jauh interaksi antara pembelajaran berbasis Kemampuan Awal Matematis (KAM) dengan peningkatan efikasi diri siswa setelah implementasi pendekatan Concrete Pictorial Abstract (CPA). Secara keseluruhan, 119 siswa sekolah dasar yang berasal dari Purwakarta, Subang, Karawang, dan Bekasi turut berpartisipasi. Baik tes maupun nontes digunakan sebagai instrument pada penelitian ini. Dengan menggunakan desain penelitian kuasi eksperimen dengan nonequivalent pretest postest control group, ANOVA dua jalur digunakan sebagai teknik analisis data. Hasil penelitian menunjukkan bahwa faktor pembelajaran lebih besar dari 0,05 yaitu (0,235), signifikansi faktor KAM lebih kecil dari 0,05 yaitu (0,030) dan signifikansi faktor interaksi (Pembelajaran KAM) lebih besar dari 0,05 yaitu (0,301). Dapat disimpulkan bahwa terdapat interaksi antara pembelajaran (CPA dan konvensional) berdasarkan KAM dan efikasi diri siswa. Dengan demikian, pendekatan CPA dapat dijadikan solusi dalam meningkatan efikasi diri siswa sehingga mereka dapat belajar dengan kepercayaan diri yang lebih tinggi.Kata kunci: concrete pictorial abstract, efikasi diri, kemampuan awal matematis.